Scaffolding pada Kesalahan Siswa dalam Menyelesaikan Masalah Open-Ended Berdasarkan Gaya Kognitif Field Dependent dan Field Independent - Innes Nurazzahra; Ali Shodikin (MATHEdunesa, 2026)
Open-ended problems require students to think deeply and use various methods and answers, but many students are not accustomed to them, which leads to their not being able to solve them correctly. Students’ errors are related to field dependent and field independent cognitive styles, which influence differences in understanding and analytical abilities, highlighting the necessity of suitable scaffolding catered to students' requirements. This study aims to describe the provision of scaffolding for students’ errors in solving open-ended problems based on field dependent and field independent cognitive styles. This study used a descriptive qualitative approach. The research subjects consisted of one field dependent student and one field independent student who made the most frequent and varied errors in solving open-ended problems. The selection of research subjects also considered equivalence in mathematical ability and the same gender. The instruments used in this study were the group embedded figures test, a mathematics ability test, an open-ended problem test, an interview and scaffolding guidelines. The research data were analyzed through three stages: data condensation, data display, and conclusion drawing. The results showed that student with a field dependent cognitive style made errors in comprehension, transformation, process skills, and encoding. The scaffolding provided included reviewing, explaining, restructuring, and developing conceptual thinking. Meanwhile, student with a field independent cognitive style made errors in comprehension, transformation, and process skills. The scaffolding provided included reviewing and restructuring. The results of the study showed that scaffolding was able to reduce errors made by field dependent student and address errors made by field independent student in solving open-ended problems.